Pengaruh Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Intern Terhadap Keandalan Laporan Keuangan di Lingkungan SKPD Kota Sabang - Faizin Wahyudi; Hasan Basri (Program Magister Akuntansi Unsyiah, 2016)
The aim of this study was to examine the effects of capacity of human resource, the use of information technology and internal control system toward the reliability of financial reporting in the SKPD of Kota Sabang. This study was a census study, where the study used all elements of the population into research data. The population used in this study was all the accounting entity in the government of Kota Sabang which amount to 34 regional work units. The respondents in this study were the Head of SKPD which amount to 34 people. The results showed that the capacity of human resource, the use of information technology and internal control systems collectively have effects on the reliability of financial reporting in the SKPD of Kota Sabang.KEYWORDS : Human Resources, Use of Information Technology, Internal Control System and Reliability of Financial reporting